Gold nanoparticle SERS substrates sustainable at extremely high temperatures. Issue 20 (12th May 2017) - Cortes Vega, Fernando D.; Martinez Torres, Pablo G.; Pichardo Molina, Juan; Gomez Ortiz, Nikte M.; Hadjiev, Viktor G.; Zarate Medina, Juan; Robles Hernandez, Francisco C.
Abstract : We report a technology for supporting gold nanoparticles (GNPS) with preserved SERS active substrates capable of sustaining extreme temperatures as high as the melting point of gold. Abstract : We report a technology for supporting gold nanoparticles (GNPS) with preserved SERS activity in substrates capable of sustaining temperatures as high as the melting point of gold. The material processing involved dispersion of citrate-capped GNPS in colloidal pseudoboehmite. The suspension was dried at 100 °C followed by annealing in air at temperatures of up to 1000 °C. Thus prepared substrates crystallized in γ-Al2 O3 or θ-Al2 O3 phases depending on the annealing temperature. XRD, TEM, and Raman spectroscopy characterizations show that GNPS remain nano-crystalline with preserved SERS activity and no apparent changes in size or shape after being treated at high temperatures. These results were also corroborated by the substrate UV-Vis absorption spectra. The SERS enhancement factor for Rhodamine 6G remained stable across the samples and showed no dependence on exposure to harsh environments.